Epidemiological Features of Spinal Cord Injury in China: A Systematic Review - Yuan, Shiyang; Shi, Zhongju; Cao, Fujiang; Li, Jiahe; Feng, Shiqing (Frontiers in Neurology, 2018)
Background: Spinal cord injury (SCI) is a severe condition that disrupts patients’ physiological, mental, and social well-being state and exerts great financial burden on patients, their families and social healthcare system. This review intends to compile studies regarding epidemiological features of SCI in China. Methods: Searches were conducted on PubMed, EMBASE, Web of Science and Cochrane Library for relevant studies published through January, 2018. Studies reported methodological and epidemiological data were collected by two authors independently. Results: Seventeen studies met the inclusion criteria. Two studies reported incidence of SCI that is 60.6 in Beijing (2002) and 23.7 in Tianjin (2004-2008). All studies showed male had a larger percentage in SCI compared to female except Taiwan (2000-2003). The average male and female ratio was 3-4:1 in China and the highest male and female ratio was 5.74: 1 in Tianjin (2004-2007). Farmers, labourers and unemployed people accounted for more than half of the SCI patients in China. Fall was the primary causation with exception of Heilongjiang (2009-2013), Beijing (2001-2010) and Taiwan (2002-2003), where motor vehicle collision (MCVs) was the leading causation. Pulmonary infection, urinary tract infection and bedsore were common complications, accounting for approximately 70% of SCI patients in China. Conclusion: This review shows that epidemiological features of SCI are various in different regions in China and prevention should be implemented by regions. The number of patients with SCI result from fall and MCVs may become a main public health problem because population aging and economic developing in China. However, because all included studies were retrospective and lacking a register system in China, some data were incomplete and some cases may be left out, so the conclusion may not be generalizable to the other regions.